Intensive Interaction Training for Paid Carers: 'Looking, Looking and Find Out When They Want to Relate to You'. Issue 4 (8th June 2016) - Nagra, Maninder K.; White, Rose; Appiah, Afua; Rayner, Kelly
Abstract : Background: Intensive interaction (II) is a communication approach useful for working with people with severe intellectual disabilities. Health and social care providers offer II training courses to paid carers working in local services with the goal of improving social communication for their clients. Materials and methods: Eight paid carers who had been trained in II were interviewed 2–3 years after training, to explore how their practice had changed, and whether any changes were sustainable. Interviews were analysed using interpretative phenomenological analysis. Results: Analysis revealed a master theme of emotional and practical endurance, with empowerment, better understanding and perceived barriers to implementation comprising subthemes. Conclusions: Despite actual and perceived barriers to the enduring use of II, all participants spoke positively of the approach and were continuing to use II in practice.